The Oxford History of Hinduism: Modern Hinduism, edited by Torkel Brekke. (22nd July 2022) - Hatcher, Brian A
Abstract : The Oxford History of Hinduism: Modern Hinduism, edited by Torkel Brekke. New York:Oxford University Press, 2019. xi + 317 pp., £73 (hb). ISBN 9780198790839.